Overcoming post-communist labour weakness: Attritional and enabling effects of multinationals in Central and Eastern Europe. (June 2014) - Lee, Aleksandra Sznajder; Trappmann, Vera
We use micro-level analysis of developments in the steel sector in Poland, Romania and Slovakia to examine the effects of multinational corporations on trade unions in Central and Eastern Europe. We argue that unions' weakness can be attributed to their strategies during the restructuring and privatization processes of post-communist transition. Tactics used for union regeneration in the West are less appropriate in the East, but revival may be possible because the power of transnational capital forces unions to focus their efforts on articulating workers' interests. We examine the emerging system of industrial relations in the sector and explore the development of capabilities needed to overcome post-communist legacies.